Once again about advantages of the new method of electromagnetic isotopes separation - Kirochkin, Yu.A.; Kirochkin, A.Yu. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2012)
The advantage of the new method of electromagnetic isotopes separation in the crossed electric and magnetic fields in comparison with an ordinary method with the presence of only magnetic field is shown in the paper. It is also shown that the theory of ordinary method of isotopes separation in the magnetic field of linear current, written in article of Bardakov V.M. etc. in ZTF, 2010, Vol. 80, No. 10, pp. 115-119, is built wrong. В работе показано преимущество нового метода электромагнитного разделения изотопов в скрещенных электрическом и магнитном полях по сравнению с обычным методом при наличии только магнитного поля. Также показано, что теория обычного метода разделения изотопов в магнитном поле линейного тока, изложенная в работе Бардакова В.М. и др. в ЖТФ, 2010, Т. 80, Вып. 10, С. 115-119, построена неверно. В роботі показана перевага нового метода електромагнітного розділення ізотопів у схрещених електричному та магнітному полях у порівнянні зі звичайним методом при наявності тільки магнітного поля. Також показано, що теорія звичайного метода розділення ізотопів у магнітному полі лінійного струму, викладена у роботі Бардакова В.М. та ін. у ЖТФ, 2010, Т. 80, Вип. 10, С. 115-119, побудована невірно.
Ще раз про переваги нового метода електромагнітного розділення ізотопів
Keywords: electromagnetic field; isotope; separation; current; trajectory; електромагнітне поле; ізотоп; розділення; струм